2018
DOI: 10.1186/s13014-018-1104-0
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced muscle fibrosis rat model: establishment and valuation

Abstract: BackgroundLack of animal model of radiation induced muscle fibrosis, this study aimed to establish such a model by using 90 Gy single dose irradiation to mimic clinical relevance and also to explore the potential post-irradiation regenerative mechanism.MethodsSD rats were randomly divided into dose investigation groups and time gradient groups. Group1–6 were irradiated with a single dose of 65Gy, 70Gy, 75Gy, 80Gy, 85Gy and 90Gy respectively, and the degree of rectus femoris fibrosis in the irradiated area was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 63 publications
2
18
0
Order By: Relevance
“…Mitochondrial dysfunction has been observed in a variety of radiation-induced diseases such as injury to the skeletal muscle and lacrimal glands and brain damage. 26,46,47 The damaged indirectly activate autophagy. [52][53][54] In this study, the ultrastructural observations indicated that radiation induced severe mitochondrial damage, apoptosis and autophagy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Mitochondrial dysfunction has been observed in a variety of radiation-induced diseases such as injury to the skeletal muscle and lacrimal glands and brain damage. 26,46,47 The damaged indirectly activate autophagy. [52][53][54] In this study, the ultrastructural observations indicated that radiation induced severe mitochondrial damage, apoptosis and autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…26 In brief, 5% pentobarbital sodium (0.1 mL/100 g) was injected intraperitoneally for anaesthesia, and then the surface of the medial rectus femoris on the left thigh was labelled using a marker. 26 In brief, 5% pentobarbital sodium (0.1 mL/100 g) was injected intraperitoneally for anaesthesia, and then the surface of the medial rectus femoris on the left thigh was labelled using a marker.…”
Section: Establishment Of the Radiation-induced Dermatitis Rat Modelmentioning
confidence: 99%
See 3 more Smart Citations